2021
DOI: 10.1002/mc.23308
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Wnt/beta‐catenin in CTNNB1‐mutated endometrial cancer

Abstract: The role of β-catenin/TCF transcriptional activity in endometrial cancer (EC) recurrence is not well understood. We assessed the impact of Wnt/β-catenin inhibition in EC models. In an analysis of the Cancer Genome Atlas, we confirmed that CTNNB1 mutations are enriched in recurrent low-risk EC and showed that aberrant Wnt/β-catenin pathway activation is associated with recurrence. We studied CTNNB1-wildtype (HEC1B, Ishikawa) and CTNNB1-mutant (HEC108, HEC265, HEC1B-S33Y, Ishikawa-S33Y) EC cell lines. Dose respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 49 publications
(134 reference statements)
2
26
0
Order By: Relevance
“…Almost 40% of UCEC cases exhibit abnormal activation of the Wnt/β-catenin pathway. It has been shown that CT-NNB1 mutations leading to activation of the Wnt signaling pathway are bound up with high-grade UCEC in young women ( 51 ). As suggested by Chen et al., inhibition of MRP4 could block the viability and survival of endometrial tumors by targeting Wnt/β-catenin pathway ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Almost 40% of UCEC cases exhibit abnormal activation of the Wnt/β-catenin pathway. It has been shown that CT-NNB1 mutations leading to activation of the Wnt signaling pathway are bound up with high-grade UCEC in young women ( 51 ). As suggested by Chen et al., inhibition of MRP4 could block the viability and survival of endometrial tumors by targeting Wnt/β-catenin pathway ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was more frequently altered in metastatic ACC, as opposed to localized stages ( Figure 2 ), suggesting that CTNNB1 could be involved in the switch to metastasis. On the targeting drug PRI-724, there are some data for HCC [ 42 ], breast cancer [ 43 ], colorectal cancer [ 44 ], endometrial cancer [ 45 ], sarcomas [ 46 ], and neuroendocrine tumors [ 47 ]. It has not been approved by the FDA yet and, to our best knowledge, has never been tested in ACC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivation of Wingless/int1 (Wnt)/ β -catenin signalling has been implicated in tumorigenesis, tumour progression, recurrence, and chemoresistance of gynaecological malignancies [ 11 , 18 20 ]. Specifically, Wnt signalling promotes metastasis and therapy resistance in ovarian cancer, plays a crucial role in tumorigenesis and recurrence in endometrial cancer, and participates in human papillomavirus (HPV) related tumorigenesis and metastasis in cervical cancer [ 21 ].…”
Section: Wnt Signalling and (Over) Expression Of β ...mentioning
confidence: 99%
“…Tumours with mutations in CTNNB1 tend to have low-grade histology, low rates of myometrial invasion with low rates of LVSI. They usually occur in women with EC at younger age, which clinically indicates a low risk of recurrence [ 11 , 18 , 20 , 48 ]. However, mutations of CTNNB1 gene are related to worse outcomes with significantly increased rate of disease recurrence and lower overall survival, compared to other tumours with low-grade histology, specifically in relation to mutations in exon 3 [ 20 , 52 ].…”
Section: Clinical Significance Of Ctnnb1 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation